Telo med opazovanjem in udeležbo - Urh, Jana (Družboslovne razprave, 2004)
Text presents arrival on the field, where ritual as unrepeatable event is observed and participated in such a way that methodological questions, objectives and problems can be raised. Body as possessed and observed occupies the attention of the anthropologist, while asking "who" and "what" can speak. Body is revealed as mortal one; it exists in the face of death, in the position of liminality, where decisions for politics of emancipation as well as politics of explanation are made. It occupies strategic position for the analyses of gathered material from the field. Author establishes a dialogue with speakers and writers of scientific texts while discussing several paradoxes of participant observation. Field is established as a surface, where body can learn to open a space for action and agency through articulation of differences without transcendence
Keywords: anthropology; antropologija; družboslovno raziskovanje; metode; terensko delo; opazovanje